Optimasi Perekrutan Strategis Melalui Big Data dan Sistem Informasi Manajemen - Tatang Supriyadi; Okta Five; Agus Riyanto; Suryatno Wiganepdo Soegoto; Trustorini Handayani (JURISMA : Jurnal Riset Bisnis & Manajemen, 2026)
Human resource management is reaching a tipping point in the digital age, as data-driven approaches are beginning to outperform traditional intuition-based hiring techniques. In order to create a framework for strategic decision-making in the hiring process, this study attempts to summarize the function of Big Data in Management Information Systems. In this study, 20 chosen publications from scholarly databases are subjected to a systematic literature review (SLR) using the PRISMA standard. According to the findings, hiring can now take on a predictive function with a person-job matching accuracy of up to 98.1% thanks to the integration of Big Data and AI in Management Information Systems. It has been demonstrated that using blockchain technology and cloud architecture increases operational effectiveness and data security. Big Data is a strategic tool that helps HR professionals become skilled data analysts by reconstructing their function. Technically, ethical governance to mitigate privacy threats and an integrated SIM infrastructure are necessary for execution. There is currently a gap in the literature about the impact of an algorithm-based recruitment approach on employee psychological elements, such as affective commitment and individual inventiveness, which has to be empirically tested in future research. Keywords: Big Data; Human Resource Management; Information System; Recruitment; Strategic Decision